2009
DOI: 10.1016/j.ajog.2008.08.053
|View full text |Cite
|
Sign up to set email alerts
|

The active management of risk in multiparous pregnancy at term: association between a higher preventive labor induction rate and improved birth outcomes

Abstract: Objective To determine if exposure of multiparous women to a high rate of preventive labor induction was associated with a significantly lower cesarean delivery rate. Study Design Retrospective cohort study involving 123 multiparas, who were exposed to the frequent use of preventive labor induction, and 304 multiparas, who received standard management. Rates of cesarean delivery and other adverse birth outcomes were compared in the two groups. Logistic regression controlled for confounding covariates. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Furthermore, the unusually low adjusted Odds Ratio (aOR) found for the association between "exposure" and CD rate (0.04) indicates the strong possibility of an underlying causal relationship [39]. Such a possibility is also suggested by the unusually strong aORs noted in previous AMOR-IPAT observational studies [24,[27][28][29][30].…”
Section: Strengths and Limitationsmentioning
confidence: 70%
See 3 more Smart Citations
“…Furthermore, the unusually low adjusted Odds Ratio (aOR) found for the association between "exposure" and CD rate (0.04) indicates the strong possibility of an underlying causal relationship [39]. Such a possibility is also suggested by the unusually strong aORs noted in previous AMOR-IPAT observational studies [24,[27][28][29][30].…”
Section: Strengths and Limitationsmentioning
confidence: 70%
“…However, a similar use of AMOR-IPAT in the setting of an RCT reported that AMOR-IPAT exposure led to a significantly lower NICU admission rate as compared to usual care. 30 In addition, all observational studies of AMOR-IPAT have included risk-based IOL in the early-term period (i.e., the 37 th of gestation) and all have reported either lower or unchanged rates of NICU admission following AMOR-IPAT exposure [18,20].…”
Section: Amor-ipat Exposed 2 Non-exposedmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of labor induction is increasing with time [8], and elective labor induction became more popular, and mostly associated with improved neonatal outcomes in certain circumstances. Accordingly, the overall rate of induction will unlikely decrease in the near future [9,10]. On the other hand, two to three fold increases in the risk of cesarean delivery was reported with induction of labor, and has contributed to the increase in cesarean rates over the last two decades [11].…”
Section: Introductionmentioning
confidence: 99%